Speed synchronization, physical workload and match-to-match performance variation of elite football players - Gonçalves, Bruno (2019)
work was supported by Project NanoSTIMA: Macro-to-Nano Human Sensing: Towards Integrated Multimodal Health Monitoring and Analytics, NORTE-01-0145-FEDER-000016, co-financed by Fundo Europeu de Desenvolvimento Regional (FEDER) - NORTE 2020.